The Effect of Probiotic on Oral Health in Children : A Systematic Literature Review - Alyah Heriandi; Joko Kusnoto; Armelia Sari Widyarman (Sriwijaya Journal of Dentistry, 2026)
Introduction: Oral health problems, particularly dental caries, continue to be a significant global health challenge for children. Caries leads to pain, infection, impaired nutrition, and affects overall well-being. Probiotics, live microorganisms with potential health benefits, have emerged as a preventive measure in pediatric dentistry, particularly in managing oral microbiota. Purpose: This review evaluates the impact of probiotics on oral health in children, focusing on caries prevention, microbiota composition, plaque, gingival health, and salivary parameters. Methods: A systematic literature review was conducted, analyzing randomized controlled trials, clinical trials, and quasi-experimental studies published between 2010 and 2025. Data was synthesized qualitatively to identify trends and outcomes across various probiotic interventions.  Results: Studies generally show that probiotics reduce cariogenic bacteria like Streptococcus mutans, improve plaque control, and enhance gingival health. However, long-term benefits for caries prevention remain inconsistent. The effectiveness of probiotics varies by strain, dosage, and delivery method. Conclusion: Probiotics hold promise as adjunctive agents in pediatric oral health care but are not a substitute for traditional oral hygiene practices. Further research, particularly long-term studies with standardized protocols, is essential to establish clear guidelines for their use in preventing caries in children.